Penerimaan LGBT oleh Tempat Ibadah - Aureliya Ramadhanti; Suzy Azeharie (Koneksi, 2020)
LGBT is a sexuality issue that is still being debated in Indonesian society, especially in the religious scope. The church,as a place of worship which is a community with the same belief to worship, has teachings with an interpretation that considers LGBT a sin. Gereja Komunitas Anugerahand the Metropolitan Community Church of Toronto are churches that openly accept LGBT congregations. The two churches are trying to support LGBT congregations by holding activities that discuss the rights of LGBT congregations. This research wants to know how the acceptance of LGBT congregations by churches as a place of worship in Indonesia. Researchers review from the communication side, communication functions and goals. The method used in this research is a phenomenological method with a qualitative descriptive approach. The research data were obtained from in-depth interviews, direct observation, document study and literature study. The conclusion of this research is that the church as a place of worship accepts LGBT because it has a meaning of the holy book verse. Acceptance is carried out by communicating with LGBT people, supporting, instilling religious values, and inviting them to be involved in activities at places of worship.LGBT merupakan isu seksualitasyang masih menjadi perdebatan di masyarakat Indonesia, khususnyapada  lingkup keagamaan. Gereja sebagai tempat ibadah yang merupakan suatu komunitas dengan kepercayaan yang sama untuk beribadah pada umumnya memiliki ajaran dengan tafsiran yang menganggap bahwa LGBT merupakan suatu dosa. Gereja Komunitas Anugerah dan Metropolitan Community Church of Torontoadalah gereja yang secara terbuka menerima jemaat LGBT.Kedua gereja tersebutberupaya mendukung jemaat LGBT dengan mengadakan kegiatan yang membahas hak jemaat LGBT. Penelitian ini ingin mengetahui bagaimanapenerimaan jemaat LGBT yang dilakukan olehgereja sebagai tempat ibadah di Indonesia. Peneliti meninjau dari sisikomunikasi, fungsi dan tujuan komunikasi. Metode yang digunakan dalam penelitian ini adalah metode fenomenologi dengan pendekatan deskriptif kualitatif. Data penelitian diperoleh dari wawancara mendalam,pengamatan langsung, studi dokumen dan studi kepustakaan. Kesimpulan penelitian ini adalahgereja sebagai tempat ibadah menerima LGBT karena memiliki pemaknaan terhadap ayat kitab suci. Penerimaan dilakukan dengan berkomunikasi dengan para LGBT, mendukung, menanamkan nilai-nilai agama, dan mengajak ikut terlibat dalam kegiatan di tempat ibadah.